Morphometric Analysis of Shanthanavardhini Watershed using GIS - Mani, N.D (International Journal of Computer Sciences and Engineering, 2025)
Morphometric analysis was carried out to estimate the characteristics of a watershed. Earlier this analysis was laborious and time consuming as they were performed manually. The advent of satellite image and Geographical Information System (GIS) had made the analysis easier. For the present study Shanthanavardhani watershed located in Dindigul District, Tamil Nadu, India was selected. The geographical area of the watershed was 71.85 Km2. Morphometric parameters were analysed in three different aspects viz., linear, relief and areal. The watershed falls in 5th basin order, the basin relief is 0.82 Km, ruggedness number is 2.19. The value of drainage density, bifurcation ratio and stream frequency of the watershed is 2.68, 3.48 and 5.07 respectively. The output of the analysis can be used for further study such as identification sites for constructing water harvesting structure, estimation of soil erosion etc